Condylar position changes after three months of treatment with posterior bite turbo - German Eduardo Puerta-Salazar; Carlos Humberto Martínez-Cajas (Universidad de Antioquia, 2020)
Introduction: all orthodontic treatments must be safe in terms of temporomandibular joint health. No reports in the recent literature evaluate the association between the use of posterior bite turbos and condylar position changes. The aim of the present study was to evaluate condylar position changes occurring after three-month treatment with posterior bite turbo in patients from the Dental School of the Universidad del Valle. Methods: a sample of 15 hyperdivergent patients was randomly distributed into two groups: Bite Turbo and Control Group. Cone-Beam Computed Tomography (CB-CT) was used to assess the condyle position before the bite turbos bonding to first and second molars, and after three months of use of the appliances. Distances were taken from the CB-CT by a single operator, and the calibration was tested with intraclass correlation (> 0.9). Results: no statistical difference between the position of left and right condyles was detected. However, there was a significant difference in the upper space of the left condyle between the initial and final measurement. Patients reported satisfactory use of the occlusal bite turbo (85.8%) in three months of treatment. Conclusion: contrary to the expected, the simultaneous use of posterior occlusal appliances with balanced mandibular movements for 3 months did not cause significant changes in condylar position. The patients tolerate well the use of occlusal stops.